2020
DOI: 10.1158/1078-0432.ccr-19-2896
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Promoter DNA Methylation in Urine and Plasma Aids the Detection of Non–Small Cell Lung Cancer

Abstract: Purpose: Low-dose CT screening can reduce lung cancer-related mortality. However, CT screening has an FDR of nearly 96%. We sought to assess whether urine samples can be a source for DNA methylation-based detection of non-small cell lung cancer (NSCLC).Experimental Design: This nested case-control study of subjects with suspicious nodules on CT imaging obtained plasma and urine samples preoperatively. Cases (n ¼ 74) had pathologic confirmation of NSCLC. Controls (n ¼ 27) had a noncancer diagnosis. We detected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…These results demonstrate that GDF15 might act as a tumor suppressor gene in colon cancer. Many mechanisms result in the inactivation of tumor suppressor genes, such as loss of heterozygosity [ 20 22 ], DNA methylation [ 23 , 24 ], or acetylation [ 25 , 26 ]. Future studies should focus on the mechanism through which GDF15 is repressed in these cells; this finding could provide new strategies for the diagnosis and gene therapy of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that GDF15 might act as a tumor suppressor gene in colon cancer. Many mechanisms result in the inactivation of tumor suppressor genes, such as loss of heterozygosity [ 20 22 ], DNA methylation [ 23 , 24 ], or acetylation [ 25 , 26 ]. Future studies should focus on the mechanism through which GDF15 is repressed in these cells; this finding could provide new strategies for the diagnosis and gene therapy of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found that hypermethylated DMRs in 3 regions (TSS200, TSS1500, and gene body) are significantly higher than hypomethylated ones. Furthermore, 15 tumor suppressor genes belonging to the HyperDown group were identified, of which CDO1 (Cysteine Dioxygenase Type 1) [ 59 , 60 ], IRF8 (Interferon Regulatory Factor 8) [ 61 ], STAT5A (Signal Transducer And Activator Of Transcription 5A) [ 62 ], CFTR (CF Transmembrane Conductance Regulator) [ 63 ], ADAMTS8 (ADAM Metallopeptidase With Thrombospondin Type 1 Motif 8) [ 64 ], WIF1 (WNT Inhibitory Factor 1) [ 65 ], GATA5 (GATA Binding Protein 5) [ 66 ], FOXA2 (FOXA2) [ 67 ], SHISA3 (Shisa Family Member 3) [ 68 ], AXIN2 (Axin 2) [ 69 ], DIRAS3 (DIRAS family GTPase 3) [ 70 ], IRX1 (Iroquois Homeobox 1) [ 71 ], and ITGA5 (Integrin Subunit Alpha 5) [ 72 ] are confirmed by previous studies to be silenced via hypermethylation in lung cancer ( Tables S1–S3 ). Although the tumor suppressor CAMK2N1 (Calcium/Calmodulin Dependent Protein Kinase II Inhibitor 1) has not been associated with lung cancer yet, its hypermethylation has been shown to promote tumorigenesis in other cancers [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…We detected meth-HOXA9 with a sensitivity of 75.0% and a specificity of 98.0% in plasma from patients with advanced lung adenocarcinoma. Liu et al [ 6 ] reported a sensitivity and specificity for plasma meth-HOXA9 of 58% and 80%, respectively, in patients suspected of NSCLC. Ooki et al [ 26 ] reported quite different results with a sensitivity and specificity of 27.9% and 92.9%, respectively, in serum from patients with stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The obvious advantages are the easy access, the overcoming of tumor heterogeneity, the minimal discomfort to the patient, and the possibility of serial measurements. It is most commonly measured in a blood sample, but other body fluids such as urine, sputum, or bronchial lavage fluid have also been suggested [ 4 , 5 , 6 ]. ctDNA can be detected as a tumor-specific somatic mutation, for example, an oncogenic driver mutation or a tumor-specific aberrantly methylated gene.…”
Section: Introductionmentioning
confidence: 99%